The Cinema of Angelopoulos and the refugee issue in the Balkans: The Suspended Step of the Stork (1991) - Werly, Patrick (Sensus Historiae, 2025)
This article is about a film that follows the investigation of a Greek TV journalist, who seeks to find out more about the refugees stranded on Greece’s northern border near Albania, waiting indefinitely for papers. Angelopoulos shows not only the extreme misery caused by this situation, but also the difficulty of getting close to people, and the article follows the allegorical thread of the film. Faced with the refugee crisis and general indifference, the director attempts to formulate a utopia that lies in dialogue between strangers rather than in the construction of an ideal society.